Pathogenicity of an Escherichia coli O115:K"V165" mutant negative for F165(1) fimbriae in septicemia of gnotobiotic pigs. - Ngeleka, M (1993)
To evaluate the role of the F165(1) fimbrial system in the pathogenesis of septicemia, 2-day-old germfree pigs were inoculated intragastrically with Escherichia coli O115:K"V165":F165 wild-type strain 5131, its F165(1)-negative TnphoA mutant M48, or E. coli O115:K(-):F165(-) wild-type strain 862B. Pigs were sacrificed at different times (3, 6, 12, 24, 48, and 96 h) postinfection (p.i.). Pigs inoculated with strain 5131 developed clinical signs (anorexia, lameness, reluctance to move, or lack of motor coordination) and were moribund within 48 h p.i., and, at necropsy, infecting bacteria were isolated in various extraintestinal organs. Strain 5131 was isolated as early as 6 h p.i. from the blood of inoculated pigs. Pigs inoculated with mutant M48 developed only mild clinical signs at 96 h p.i. Mutant M48 colonized extraintestinal organs of pigs but to a lesser extent than the parent strain did. In contrast to the parent strain, this mutant was not isolated in the blood of inoculated pigs. Pigs inoculated with strain 862B remained normal during the experiment. All of the strains colonized the mucus layer of the intestine, but no histological changes of intestinal mucosa were observed by either light or electron microscopy. The parent strain, but not the mutant M48, expressed F165(1) in vivo. In a competitive study in which the parent strain and its afimbrial mutant were inoculated simultaneously, clinical signs of septicemia developed 24 h after inoculation, and only the parent strain 5131 was isolated from the blood of inoculated pigs. Our results suggest that the F165(1) fimbrial system of E. coli O115:K"V165" strains may play an important role in the ability of the bacteria to survive in the blood and spread systemically through the porcine host.